2018
DOI: 10.1016/j.ultsonch.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Alkanethiol self-assembling on gold: Influence of high frequency ultrasound on adsorption kinetics and electrochemical blocking

Abstract: Self-assembling of undecanthiol (C11SH) on polycrystalline gold was investigated under two different conditions. The kinetics of C11SH grafting was studied without and under high frequency ultrasound irradiation. Two electrochemical experiments were extensively carried out in order to determine electrochemical surface blocking of adsorbed layers as a function of grafting time: chronoamperometry in-situ monitoring and cyclic voltammetry. Interestingly, the grafting process is highly accelerated under sonication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Such cavitation reorientation has been suggested by Atobe et al [18] and seems to be experimentally confirmed by our works. On the contrary, agitation generated by acoustic activity is noxious for the SAM grafting process, as showed in previous studies [11] .…”
Section: Resultsmentioning
confidence: 50%
See 4 more Smart Citations
“…Such cavitation reorientation has been suggested by Atobe et al [18] and seems to be experimentally confirmed by our works. On the contrary, agitation generated by acoustic activity is noxious for the SAM grafting process, as showed in previous studies [11] .…”
Section: Resultsmentioning
confidence: 50%
“…Cyclic voltammetry experiments were carried out in acetonitrile with 10 mM ferrocene and 0.2 M of lithium perchlorate (supporting salt) at 100 mV/s. X-Ray Photoelectrons Spectroscopy (XPS) and Polarization-Modulation Infrared Reflection Absorption Spectroscopy (PM-IRRAS) apparatuses were described in previous work [11] .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations